2010
DOI: 10.1068/p6560
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Faces: Quantifiable Visual Cues to Weight

Abstract: Body weight plays a crucial role in mate choice, as weight is related to both attractiveness and health. People are quite accurate at judging weight in faces, but the cues used to make these judgments have not been defined. This study consisted of two parts. First, we wanted to identify quantifiable facial cues that are related to body weight, as defined by body mass index (BMI). Second, we wanted to test whether people use these cues to judge weight. In study 1, we recruited two groups of Caucasian and two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(140 citation statements)
references
References 37 publications
9
127
1
3
Order By: Relevance
“…A number of studies have suggested that changes in facial shape are correlated with overall body mass and that it is possible to estimate overall body mass from the face alone 42. However, the relationship between facial shape and the BMI of the individual is weaker than is found for the equivalent torso shape change, and judgements of overall body mass based on facial cues are also less precise than judgements based on the rest of the body 42.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that changes in facial shape are correlated with overall body mass and that it is possible to estimate overall body mass from the face alone 42. However, the relationship between facial shape and the BMI of the individual is weaker than is found for the equivalent torso shape change, and judgements of overall body mass based on facial cues are also less precise than judgements based on the rest of the body 42.…”
Section: Discussionmentioning
confidence: 99%
“…BMI has been shown to correlate with fWHR [11,30] and may implicate behavioural associations. Here, we find no association between BMI and fWHR (r ¼ 0.09, p ¼ 0.35) but BMI was significantly positively correlated with dominance (r ¼ 0.22, p ¼ 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…R. Soc. B 371: 20150380 provide targets for testing their relationship to health outcomes (width-to-height-ratio, perimeter-to-area ratio and cheek-tojaw-width ratio) [31]. These three measures do not necessarily capture all aspects of face shape that relate to weight perceived from faces.…”
Section: (C) Facial Adipositymentioning
confidence: 99%